Liver Transplantation for Hepatocellular Carcinoma: Malatya Experience - Ince, V; Akbulut, S; Otan, E; Ersan, V; Karakas, S; Sahin, TT; Carr, BI; Baskiran, A; Samdanci, E; Bag, HG; Koc, C; Usta, S; et al. (2020)
The original version of this article unfortunately contained a mistake in the author group section. C1 [Ince, Volkan; Akbulut, Sami; Otan, Emrah; Ersan, Veysel; Karakas, Serdar; Sahin, Tolga Tevfik; Carr, Brian, I; Koc, Cemalettin; Usta, Sertac; Ozdemir, Fatih; Barut, Bora; Gonultas, Fatih; Sarici, Baris; Kutluturk, Koray; Dogan, Murat Sait; Ozgor, Dincer; Dirican, Abuzer; Aydin, Cemalettin; Isik, Burak; Ara, Cengiz; Kayaalp, Cuneyt; Emre, Sukru; Yilmaz, Sezai] Inonu Univ, Liver Transplantat Inst, Dept Surg, TR-44315 Malatya, Turkey. [Samdanci, Emine] Inonu Univ, Sch Med, Dept Pathol, Malatya, Turkey. [Bag, Harika Gozukara] Inonu Univ, Sch Med, Dept Biostat, Malatya, Turkey. [Dikilitas, Mustafa] Inonu Univ, Sch Med, Dept Med Oncol, Malatya, Turkey. [Harputluoglu, Murat; Aladag, Murat] Inonu Univ, Sch Med, Dept Gastroenterol, Malatya, Turkey. [Kutlu, Ramazan] Inonu Univ, Sch Med, Dept Radiol, Malatya, Turkey. [Varol, Ilknur] Inonu Univ, Sch Med, Dept Pediat Gastroenterolgy, Malatya, Turkey.